Na(+)/H(+ )exchanger regulatory factor 1 inhibits platelet-derived growth factor signaling in breast cancer cells - Pan, Yong (BioMed Central, 2008)
INTRODUCTION: The gene encoding Na(+)/H(+ )exchanger regulatory factor 1 (NHERF1) is a putative tumor suppressor gene that harbors frequent loss of heterozygosity (LOH) and intragenic mutations in breast carcinoma. The exact biologic activity of NHERF1 in mammary glands, however, remains unclear. It was recently proposed that NHERF1 forms a ternary complex with platelet-derived growth factor receptor (PDGFR) and phosphatase and tensin homolog (PTEN), linking NHERF1 suppressor activity to PDGF-initiated phosphoinositide-3 kinase (PI3K)/PTEN signaling. METHODS: The effect of NHERF1 on the kinetics of PDGF-induced Akt activation was determined in cells with varied NHERF1 background. Levels of active Akt in mammary gland of NHERF1 knockout and wild-type mice were compared. We also examined how NHERF1 expression status affects cell sensitivity to PDGFR inhibitor. A plausible connection between NHERF1 and PTEN pathway was explored at the genetic level. RESULTS: We showed that NHERF1, through its PDZ-I domain, interacts directly with the carboxyl-terminal tail of PTEN. Knocking down NHERF1 expression in Zr75.1 cells markedly delayed the turnover of PDGF-induced phospho-Akt. Conversely, NHERF1 over-expression in MCF10A cells led to accelerated phospho-Akt degradation. The slowed decay of phospho-Akt that resulted from NHERF1 loss was evident in mouse embryonic fibroblasts isolated from NHERF1 knockout mice. In agreement with this, mammary gland tissues from these mice exhibited markedly elevated phospho-Akt. The responses of breast cancer cells to PDGFR inhibition were also altered by changes in NHERF1 expression level. Zr75.1 cells with NHERF1 knockdown were more resistant to STI-571-induced apoptosis than parental cells. Similarly, over-expression of NHERF1 rendered MCF10A cells more sensitive to STI-571. NHERF1-induced apoptotic response relies on an intact PTEN pathway; over-expression of NHERF1 in MCF10A cells with PTEN knockdown did not affect STI-571 sensitivity. It was found that NHERF1 LOH-positive breast cancer cells had reduced NHERF1 expression. Interestingly, these cells more frequently had wild-type PTEN or PI3KCA gene than the LOH-negative lines. CONCLUSION: Our data indicate that the interaction of NHERF1 with PTEN counterbalances PI3K/Akt oncogenic signaling and may affect how cells respond to PDGFR inhibition in breast cancer. The dependence of NHERF1 responses on PTEN and genetic segregation of NHERF1 and PTEN (or PI3KCA) alterations suggest that NHERF1 is an active component of the PTEN pathway. Collectively, our study indicates that the biologic activity of NHERF1 in mammary gland is related to PTEN signaling.